Reflective Study of Information Technology Utilization in Maternal Anemia Prevention Programs - Shania Salsabilla alamsyah; Yanuar Fajrul Falah; Ananda Arum Dwi Puspita Sari; Nur Ayu Sekar Arum Sari; Izzatul Arifah (Jurnal Kesehatan, 2023)
Introduction: Anemia is one of the country's top health concerns that must be addressed immediately. The use of information technology (IT) in anemia prevention programs has received little attention in Indonesia. The purpose of the study was to reflect on the experience and consider the limitations and challenges encountered by the team while conducting an IT-based maternal anemia prevention program in Puskesmas Sangkrah, Surakarta. Method: this study was a qualitative study using a case study approach. The data collection methods were reflective writing and interviews. Data validity is achieved through the triangulation of data sources. Content analysis is being used to analyze data. Results: for health providers and participants of the program, it is a new challenging experience of online educational sessions. However, some obstacles and challenges are felt, including the lack of enthusiasm of participants during online education sessions, the lack of engagement between managers and participants in implementing online education compared to offline, and technical constraints from the application. Conclusion: the utilization of information technology in the maternal anemia prevention program has produced positive results, but there are still challenges that can be overcome if the approach is applied to other health programs.